2019
DOI: 10.1177/0272431619847523
|View full text |Cite
|
Sign up to set email alerts
|

School Relations and Solitude in Early Adolescence: A Mediation Model Involving Rejection Sensitivity

Abstract: Rejection sensitivity (RS) is a cognitive and affective disposition to defensively expect, perceive, and overreact to signs of rejection by others. The current study examined the role of RS as a mediating mechanism underlying the relation between school relations with peers and teachers and solitude in early adolescence. Italian middle school students ( N = 656; females = 50.9%; [Formula: see text]) reported their RS, quality of relationships with their friends and teachers, peer-related loneliness, and attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…There are several reasons to believe that cybervictimization can promote rejection sensitivity. First, Downey and Feldman [ 15 ] demonstrated that the experience of rejection could develop into some form of “basic mistrust” about interpersonal relationships, which leads to higher rejection sensitivity [ 19 , 20 ]. Second, although little study has examined the impact of cybervictimization on rejection sensitivity directedly [ 17 ], several studies have indicated that adolescents that often suffer from cyberbullying develop a low social self-perception and make a negative evaluation of their own social ability, which leads to the development of social anxiety [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several reasons to believe that cybervictimization can promote rejection sensitivity. First, Downey and Feldman [ 15 ] demonstrated that the experience of rejection could develop into some form of “basic mistrust” about interpersonal relationships, which leads to higher rejection sensitivity [ 19 , 20 ]. Second, although little study has examined the impact of cybervictimization on rejection sensitivity directedly [ 17 ], several studies have indicated that adolescents that often suffer from cyberbullying develop a low social self-perception and make a negative evaluation of their own social ability, which leads to the development of social anxiety [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ever changing social distancing directions, including school closures and working from home orders, have introduced high levels of uncertainty regarding the potential for social contact. Indeed, isolation is likely to be interpreted by rejection sensitive individuals as a rejection signal (Molinari et al, 2020). As a group, adolescents feel social rejection particularly keenly (Sebastian et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant differences were found for the psychological distress variable, which was found to be equivalent in the five sociometric types. Previous research has linked rejection in school to emotional problems such as anxiety symptoms [ 26 ], depression, feelings of loneliness and stress [ 55 ], and low satisfaction with life [ 21 , 22 ]. It is important to highlight that this study analyzes group organization and the position occupied in same by each student based on the choices and rejections made with respect to their peers according to the criterion of group work in school [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous findings suggest that the lack of social acceptance by peers is a traumatic experience, associated with a negative assessment of one’s life [ 21 , 22 ] and with greater emotional distress [ 4 , 23 ]. The lack of social acceptance by peers has also been linked to externalizing problems in adolescence [ 24 , 25 ], higher levels of anxiety [ 26 ], anger and hostility [ 6 ]. Some authors also report that adolescents who are less integrated in the classroom are precisely the ones more frequently involved in violent behavior towards their peers in the school environment [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%